Comparison of epicardial vs. endocardial reimplantation in pacemaker-dependent patients with device infection. Issue 4 (3rd June 2017) - Perrin, Tilman; Maille, Baptiste; Lemoine, Coralie; Resseguier, Noémie; Franceschi, Frédéric; Koutbi, Linda; Hourdain, Jérôme; Deharo, Jean-Claude
Abstract: Aims: Reimplantation of cardiac implantable electronic devices (CIEDs) after extraction due to device infection is a major issue in pacemaker-dependent patients. We compared in-hospital and long-term outcomes with two techniques: epicardial reimplantation (EPI) before CIED extraction and temporary pacing (TP) with a view to delayed endocardial reimplantation. Methods and results: Two cohorts of consecutive pacemaker-dependent patients who underwent transvenous lead extraction at our tertiary centre were included in this retrospective cohort study. According to successive policies, either the EPI or the TP approach was used. In-hospital complications occurred at similar rates in the EPI ( n = 59) and TP ( n = 52) cohorts (37.3% vs. 32.7%, respectively; P = 0.61). Thirteen (25.0%) patients in the TP cohort eventually were reimplanted epicardially, mainly because of infection of the temporary lead. Finally, 65 patients were discharged with an epicardial device and 37 with an endocardial device. Median follow-up was 41.7 (interquartile range 34.1–51.5) months. No difference was observed in long-term mortality according to the reimplantation strategy, but use of TP was associated with a reduced risk of late endocarditis and device reintervention (hazard ratio (HR) 0.25, 95% confidence interval (CI) 0.09–0.069, P = 0.01), whereas epicardial device reimplantation was associated with an increased risk (HR 3.62, 95% CI 1.07–12.21, P = 0.04). Conclusion: We observed similar in-hospital outcomes in our EPI and TP cohorts. Twenty-five percent of the patients initially paced by a TP strategy finally needed an epicardial device, mainly because of infection of their TP lead. Use of TP resulted in lower rates of late endocarditis and device reintervention.